The Effect of Work-Life Balance and Compensation on Turnover Intention Among Generation Z Employees in Jakarta - Laelatul Qodriyah; Agung Surya Dwianto (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of work-life balance and compensation on turnover intention among Generation Z employees in Jakarta. The increasing intention to change jobs among the younger generation poses a serious challenge for companies, particularly in retaining potential employees amid intense urban labor market competition. This study employed a quantitative approach with an explanatory method, involving 216 Generation Z employees aged 18–28 years working in various industrial sectors in Jakarta. Data were collected through an online questionnaire using purposive sampling and analyzed using multiple linear regression. The results show that work-life balance has a negative and significant effect on turnover intention. The better the balance between work and personal life, the lower the employees’ intention to leave the organization. In addition, compensation also has a negative and significant effect on turnover intention, indicating that fair and competitive compensation can reduce employees’ intention to change jobs. Simultaneously, both variables have a significant effect on turnover intention, with a coefficient of determination (R²) of 0.647, meaning that work-life balance and compensation explain 64.7% of the variation in turnover intention, while the remaining 35.3% is influenced by other factors beyond the scope of this study. These findings highlight the importance of human resource management strategies that emphasize work-life balance and competitive compensation to improve employee retention among Generation Z in urban work environments.